Determinants of unintended pregnancies among nursing mothers in southwest Nigeria. (2nd April 2020) - Afolabi, Adebukunola Olajumoke; Olaogun, Adenike Ayobola; Afolabi, Kolade Afolayan; Afolabi, Esther Kikelomo
Abstract : Background/aims: Studies have identified risks for unintended pregnancies, globally and in Nigeria, which include ineffective contraception, strong opposition to family planning by partners, number of living children and birth interval. These factors have contributed to the increasing rate of unintended pregnancy and the high rate of induced abortion, with associated consequences such as obstetric haemorrhage, infection and increased maternal morbidity and mortality. However, there is a paucity of information regarding the influence of culture and religion on pregnancy intentions. This study aimed to examine the influence of culture, religion, sociodemographic characteristics, and reproductive characteristics on nursing mothers' perception of unintended pregnancy in southwest Nigeria. Methods: This study used a sequential explanatory mixed-method approach, with both quantitative and qualitative elements. A conceptual hierarchical model was used to analyse the influence of three levels of characteristics (sociodemographic, religious and cultural, reproductive) on unintended pregnancy in southwest Nigeria. A total of 400 nursing mothers attending either a postnatal, immunisation, infant welfare or under-five clinic were selected via multistage sampling from primary healthcare centres. Quantitative data were collected from these participants using a semi-structured questionnaire, administered by a researcher. These data were analysed using both bivariate and multivariate analysis. First, they were analysed with either a chi-squared or Fisher exact test, then subjected to a regression model analysis. Qualitative data were collected and subjected to content analysis via focus group discussions with a total of 32 purposively selected participants. Results: Approximately 36.5% participants reported their index pregnancy as being unintended. With regression analysis, age (25–34 years: relative risk ratio=0.42, P =0.02; 35–44 years: relative risk ratio=0.21, P =0.003), parity (relative risk ratio=10.38, P <0.00), ethnicity (relative risk ratio=0.13, P =0.002) and religion (relative risk ratio=0.26, P =0.048) were found to be significant risk factors for unintended pregnancy. Conclusions: Age, parity, ethnicity and religion were the main determinants of unintended pregnancies. Intervention programmes should therefore be aware of these variables and address myths and misconceptions about pregnancy intentions.